1993
DOI: 10.1055/s-0038-1649576
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Activating Properties of Murine Monoclonal Antibodies to β2-Glycoprotein I

Abstract: SummaryPreviously developed murine monoclonal antibodies (MAbs) to human β2-glycoprotein I (β2GPI), a plasma protein required for the binding of anti-phospholipid antibodies, were studied for anti-platelet reactivity and influence on platelet function. The six MAbs (IgG1 isotype) tested interacted with both intact and fixed platelets in a β2GPI-dependent manner. Carbamylated β2GPI was still recognized by MAbs but was unable to mediate platelet- antibody binding. MAbs induced aggregation and secretion responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
1
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(54 citation statements)
references
References 19 publications
0
52
1
1
Order By: Relevance
“…The prothrombotic properties of aPL may be explained in part by their ability to enhance the activation of platelets. Moreover, aPL have been shown to increase production of TXB 2 in the presence of low doses of ADP, collagen, or thrombin (7,10,26,27). A recent study by our group showed a significant increase in the expression of activated glycoprotein IIb/IIIa on platelets treated with aPL and TRAP (8).…”
Section: Discussionmentioning
confidence: 88%
“…The prothrombotic properties of aPL may be explained in part by their ability to enhance the activation of platelets. Moreover, aPL have been shown to increase production of TXB 2 in the presence of low doses of ADP, collagen, or thrombin (7,10,26,27). A recent study by our group showed a significant increase in the expression of activated glycoprotein IIb/IIIa on platelets treated with aPL and TRAP (8).…”
Section: Discussionmentioning
confidence: 88%
“…This complication seems to be a consequence of platelet activation initiated when platelet Fc␥RIIa are crosslinked by antibodies (5,32). Since the interaction of IgG2-containing antibodies with Fc␥RIIa is allotype-dependent (8), it has been hypothesized that the high-binding H131 allele would be overrepresented among subjects with antibodymediated thrombosis (11,33).…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between the pathogenic effects in the passive transfer experiments and the in vitro adherence assays was not complete. These findings could be explained by the multiple effects of aCL on hemostasis, including activation of platelets, 16 induction of tissue factor, 31 and so on. Furthermore, the effect of the mAbs on the EC seems to be multifactorial and probably is not restricted merely to expression of the three adhesion molecules that were evaluated.…”
Section: Clinical Parameters In Pregnant Micementioning
confidence: 99%
“…The role of aCL in conferring the prothrombotic predisposition in APS has been strengthened by in vitro studies showing their platelet- 16,17 and EC- 18,19 activating properties. Additionally, it has been demonstrated that passive transfer 20 or active immunization 21 with aCL of naive mice led to the clinical manifestations of APS.…”
mentioning
confidence: 99%